The effect of diet composition, a probiotic and a symbiotic treatment on the ileal microbiota composition of one-week-old broiler chickens - Such, Nikoletta; Farkas, Valéria; Molnár, Andor; Csitári, Gábor; Pál, László; Rawash, Mohamad Ali; Husvéth , Ferenc; Dublecz, Károly (Acta Agraria Debreceniensis, 2021)
A healthy microbiota present in the small intestine contributes significantly to small intestinal function, including digestion, nutrient absorption and health. The current study investigated the effects of a prebiotic, a probiotic and a symbiotic supplementation on ileal microbiota composition of broilers at 7 days of age. In a total of 574 male Ross 308 day-old chickens were divided into four groups using six replicate pens and 24 chickens per pen. A maise-soybean based control diet (C), a control diet supplemented with probiotics (Broilact; Br), a control diet supplemented with symbiotic (inulin, yeast, Bacillus subtilis; Sy) and a wheat based diet supplemented with wheat bran (W) were formulated. On day 7 of life, two chickens per pen were slaughtered and ileal chymus samples were collected. For microbiota analysis 16S rRNA (V3-V4 region) gene targeted Illumina MiSeq sequencing was used. Feeding all diets supplemented increased the diversity to varying degrees compared to the control (C) diet (p=0.006). As a conclusion, all supplementation substantially influenced ileal microbiota of broiler chickens at an early age. All these results could offer some information for the future study on the relationship between early intestinal microbiota and the compounds of the feed.